Triforis delicatula Thiele 1912 ... - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Triforis delicatula Thiele, 1912 Triforis delicatula Thiele, 1912: 305, pl. 12, fig. 30. Triphora delicatula Thiele, 1912 — Engl 2012: 298, pl. 44, fig. 1a–c. Type locality. Antarctica, Davis Sea, 66°02’09”S — 89°38’05”E, 385 m deep. Type material. Not found (Albano & Bakker 2016). Distribution. Antarctica (Thiele 1912; Engl 2012; Albano & Bakker 2016). Remarks. The specimens in the Museum für Naturkunde in Berlin do not apparently belong to the type series (Albano & Bakker 2016). ... : Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 60, DOI: 10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536 ...